DIFFERENCE OF SGOT AND SGPT LEVEL IN STADIUM IIB-IIIB SQUAMOUS CELL CERVICAL CANCER PATIENTS BEFORE AND AFTER CHEMOTHERAPY AT SANGLAH HOSPITAL DENPASAR - R. Noviyani (Institute for Research and Community Services Udayana University, 2018)
Objective:Cervical cancer became Indonesia’s highest prevalent gynecological cancer in 2013 and the highest prevalent gynecological cancer at Sanglah Hospital.Paclitaxel Carboplatin is one of the regimens used for cervical cancer treatment at Sanglah Hospital, Denpasar. Aside of providing therapeutic effect, this regimen also causes hepatotoxicity. This research was trying to determine the toxic effect of Paclitaxel Carboplatin towards liver function based on the difference of SGOT and SGPT levels before chemotherapy cycle I and after chemotherapy cycle VI. Method:This wasa prospective observational research with a study case method conducted from January 2017 until June 2017 at Obstetric Polyclinic of Sanglah Hospital, Denpasar.Samples’ SGOT and SGPT level before and after chemotherapy I and VI were recorded and were then analysed with Shapiro-Wilk normality test. If the data were distributed normally, they would undergo tpaired test and Wilcoxon test at 95% confidence level if they were not distributed normally. Results: Tenpatients fulfilled the research criteria. There was a meaningless increase for SGOT level (p=0.575) along with a meaningless increase for SGPT level (p=0.074) before and after Paclitaxel Carboplatin chemotherapy cycle I and VI respectively.Conclusion: Research of toxic effect from Paclitaxel Carboplatin chemotherapy in 10 squamous cell cervical cancer patients showed a meaningless difference of both SGOT and SGPT level with the value of p>0.05 in stadium IIB-IIIB squamous cell cervical cancer patients before and after Paclitaxel Carboplatin chemotherapy cycle I and VI respectively.